Status and Distribution of Waterbirds in a Natura 2000 Area: The Case of Gialova Lagoon, Messinia, Greece - Maneas, Giorgos; Bousbouras, Dimitris; Norrby, Viggo; Berg, Håkan (Frontiers in Ecology and Evolution, 2020)
Located at the south-western most part of the Balkan peninsula, along an important migration route (the Mediterranean/Black Sea Flyway), the Gialova Lagoon wetland is one of the few remaining Important Bird Areas along the south-west coast of Greece, also designated as a Special Protection Area. The wetland serves as the first suitable stopover for many spring migrants who have flown non-stop over the Mediterranean Sea, and the last before their journey back to Africa in the autumn. In this study, we conducted monthly field visits during the period October 2016 to January 2019, with the aim to complement existing information about the site, to evaluate the current status and distribution of waterbirds, to provide insights for the management of the area and to re-assess the IBA/Ramsar criteria. A total of 149 bird species representing 43 families and 15 orders were recorded, including 36 threatened species at an International, European or/and national level, and 40 species listed in the Annex I of the EUs Birds Directive (21 species were listed as both threatened and under Annex I). 81 species were identified as wetland related species, of which 66 species were identified as waterbirds (7 orders, 11 families). Waterbirds richness and abundance were higher during the Wet season and corresponding periods (Wintering and Spring migration). All parts of the wetland supported waterbirds and threatened species, with the S. Wetland sub-area being the most diverse during the Breeding/ Nesting, and both migration periods. The abundance of most waterbirds and IBA species have declined over the last 20 years, but this does not necessarily mean that the area no longer fulfils Ramsar criterion 6 (and equivalent IBA criterion A4i). However, this outcome should not be overlooked by the site managers and conservation actions such as the restoration of fresh water inflows, which could improve habitats and water conditions for IUCN and IBA species, should be implemented with high priority. In addition, our results indicate that the area meets Ramsar criterion 4 and criterion 2, and thus we suggest that it should be further investigated and evaluated to potentially become the eleventh Greek Ramsar site